Care‐Delivery Interventions to Manage Agitation and Aggression in Dementia Nursing Home and Assisted Living Residents: A Systematic Review and Meta‐analysis. Issue 3 (March 2016) - Jutkowitz, Eric; Brasure, Michelle; Fuchs, Erika; Shippee, Tetyana; Kane, Rosalie A.; Fink, Howard A.; Butler, Mary; Sylvanus, Tonye; Kane, Robert L.
Abstract : Objectives: To evaluate the efficacy of nonpharmacological care‐delivery interventions (staff training, care‐delivery models, changes to the environment) to reduce and manage agitation and aggression in nursing home and assisted living residents. Design: Three bibliographic databases, references of systematic reviews, ClincalTrials.gov, and the International Controlled Trials Registry Platform were systematically searched for randomized controlled trials reporting behavioral outcomes for nonpharmacological care‐delivery interventions in nursing homes and assisted living facilities. Five investigators independently assessed study eligibility, extracted data, rated risk of bias, and graded strength of evidence. Inclusion was limited to studies with low to moderate risk of bias. Setting: Nursing homes and assisted living facilities. Participants: Facility caregiving staff. Measurements: Agitation, aggression, antipsychotic and other psychotropic use, general behavior. Results: Nineteen unique studies met entry criteria, addressing several categories of facility caregiver training interventions: dementia care mapping (DCM; n = 3), person‐centered care (PCC; n = 3), clinical protocols to reduce the use of antipsychotic and other psychotropic drugs (n = 3), and emotion‐oriented care (n = 2). Eleven additional studies evaluated other unique interventions. Results were pooled for the effect of each type of intervention on agitation and aggression: DCM (standardized mean difference −0.12, 95% confidence interval (CI) = −0.66 to 0.42), PCC (standardized mean difference −0.15, 95% CI = −0.67 to 0.38), and protocols to reduce antipsychotic and other psychotropic use (Cohen‐Mansfield Agitation Inventory mean difference −4.5, 95% C = −38.84 to 29.93). Strength of evidence was generally insufficient to draw conclusions regarding efficacy or comparative effectiveness. Conclusion: Evidence was insufficient regarding the efficacy of nonpharmacological care‐delivery interventions to reduce agitation or aggression in nursing home and assisted living facility residents with dementia.